Toughing It Out in Afghanistan - O'Hanlon, Michael E. (Book collections on Project MUSE., 2010)
Is Afghanistan another Vietnam, a quagmire that the United States should escape as soon as possible? Or is it a crucial war than can and must be won? The authors acknowledge current difficulties in Afghanistan but also explicate how the war-torn country can emerge as a stable sovereign nation, free from the yoke of the Taliban and al Qaeda.